2018
DOI: 10.1111/liv.13640
|View full text |Cite
|
Sign up to set email alerts
|

How to improve access to therapy in hepatitis B patients

Abstract: Despite the availability of a preventive vaccine and active antiviral treatments that stop disease progression and reduce the risk of hepatocellular carcinoma, hepatitis B is still a major public health problem. Only an estimated 10% of the 257 million people living with HBV have been diagnosed and as few as 1% are being adequately treated. Barriers to diagnosis and treatment include: (i) limited awareness and lack of knowledge about HBV infection and HBV‐related diseases; (ii) under‐diagnosis with insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
1
27
0
2
Order By: Relevance
“…[ [7][8] It is estimated that in China there are 20-30 million people with CHB, 1 million with liver cirrhosis and 0.3 million with HCC caused by hepatitis B. [ 9] Deaths due to HBV-related liver diseases in China (0.308 million deaths per year) account for more than 30% of the global mortality from HBV (0.887 million deaths per year) [ 10] . The antiviral therapy is the primary link to slow the conversion of CHB into cirrhosis, which can effectively restore liver function and improve survival rate in patients with CHB.…”
Section: Abstract Chronic Hepatitis B Cirrhosis Traditional Chinesementioning
confidence: 99%
See 1 more Smart Citation
“…[ [7][8] It is estimated that in China there are 20-30 million people with CHB, 1 million with liver cirrhosis and 0.3 million with HCC caused by hepatitis B. [ 9] Deaths due to HBV-related liver diseases in China (0.308 million deaths per year) account for more than 30% of the global mortality from HBV (0.887 million deaths per year) [ 10] . The antiviral therapy is the primary link to slow the conversion of CHB into cirrhosis, which can effectively restore liver function and improve survival rate in patients with CHB.…”
Section: Abstract Chronic Hepatitis B Cirrhosis Traditional Chinesementioning
confidence: 99%
“…The antiviral therapy is the primary link to slow the conversion of CHB into cirrhosis, which can effectively restore liver function and improve survival rate in patients with CHB. [1 [1][2][3][4][5][6][7][8][9][10][11][12] Currently, the US Food and Drug Administration (FDA) has approved two types of anti-hepatitis B virus drugs: interferon (IFN) and nucleos(t)ide analogs (entecavir, lamivudine, telbivudine, adefovir, and tenofovir), although nucleoside analogues are well tolerated and exhibit an early and potent antiviral effect, the selection of resistant mutants and nephrotoxicity during long-term therapy limit their use. [ [13][14] Chinese herbal medicine (CHM), as one of the most popular complementary and alternative therapies of CHB, a large number of studies have reported its anti-hepatitis B virus effect.…”
Section: Abstract Chronic Hepatitis B Cirrhosis Traditional Chinesementioning
confidence: 99%
“…It has become a major issue in the eld of hepatology due to its rising incidence and ultimate fatality [2]. Among Asian populations, the major underlying disease for ACLF is hepatitis B virus (HBV) infection [3], which is responsible for an estimated 887,000 deaths worldwide in 2015 [4] and ranks seventh in the top causes of mortality worldwide [5].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время недостаточно данных о дальнейшем течение заболевания после прекращения терапии при длительном использовании НА у пациентов с ХГВ HBeAg-негативным, в частности о частоте развития рецидивов и необходимости продолжения ПВТ [16,17].…”
Section: Introductionunclassified